A case study user's affective preference of interior lighting in selected condominium spaces - Juarez, Lizza Magdalena E.
Condominium lighting, a very important design element in interiors must be studied and planned appropriately. This descriptive case study evaluated selected condominium general lighting conditions; affective preferences pertaining to light feature that are pleasurable to users and user's response to recommended lighting systems. This qualitative descriptive research looked at purposively handpicked 11 respondents and five interior areas of their units. The multi-method of triangulation in collecting data for this case study was a combination of observation, survey questionnaire and interview that established the strength and reliability necessary for the study. The hierarchy of consumer needs by Jordan(2000) was used as a guide to determine the light features of function and pleasure. Focusing on the users' reaction and preference towards general lighting features, the research was linked with a modified theory of affective preference (De Rouvray et al., 2008). Out of the 11 respondents, one was handpicked for a light test that further evaluated how the user related to a recommended lighting system and overall affect of general lighting of the unit. Results show that there is a failure and non-conformance in the application of proper general lighting in all 11 units and majority of its interior areas. Light feature function had overall great affect for its "sufficient lighting" based on the respondents' activities, tasks, purpose and use of interior areas. Findings indicate that the recommended average illumination levels and recommended light color appearance did not only meet lighting standards and conformance but at the same time affect greatly the subjective and unconscious preference of the user. As a recommendation, studies on lighting and users' affective preference with wider sampling range are encouraged to further affirm such lighting recommendation. Such recommendations can be incorporated in the planning, designing and application of general lighting in condominium units and other related compact living environments.